Asking questions to OBC as a category - Singh, Asha; Donald, Nidhin (Prabuddha: Journal of Social Equality; Vol 3 No 1 (2019): Has capitalism destroyed Caste and Race; does capitalism equalize or perpetuate age-old inequalities?, 2019)
This paper would try to understand the journey of OBC as a governmental category to underline some of the limitations and possibilities. Building on what has already been achieved; this paper would attempt to provide further clarifications on the history of ‘identifying and enlisting’ backward classes, pointing out underlying sociological assumptions and contradictions. The aim would be to flesh-out some of the fundamentals which inform the term ‘backward’ and its growth. In the second part of the paper, the first author (Asha Singh) would reflect on how could one begin to understand the relationship between OBC women and the category, drawing insights primarily (but not exclusively) from Bhojpuri region. Such reflections fully understand that there is no ready-made community called ‘OBC women’, rather we only have women (as a part of castes/tribes) listed as OBC, often without any real consequence in their lives.